Analisis Strategi Pemasaran Kampus Swasta Di Kota Samarinda (Studi Pada Universitas Widya Gama Mahakam Samarinda) - M. Zamroji Almursyid (CV. Multi Kreasi Media, 2023)
Marketing is one of the most important things in the business world. This includes higher education services which are increasingly mushrooming. The research to be carried out is qualitative in nature. This study emphasizes the descriptive aspects sourced from the marketing team owned by private universities. From the explanation of the resource persons, the researcher will group and classify and analyze what techniques are used to do marketing for the campus. The proposed research aims to find out what technique, how the process is, the target market and the management of the marketing mix owned by the village. Based on the results of the research and discussion carried out, it can be concluded as follows: 1. Based on the observations of the Widya Gama Mahakam Samarinda campus, it has carried out and made a good strategic marketing process from analyzing the marketing situation, designing marketing strategies, developing marketing programs and implementing well, followed by strict evaluation so that the objectives of the promotion are successful or achieved 2. The development of marketing programs carried out by providing scholarship information is able to provide a very large opportunity for the success of the promotion team 3. The campus is able to provide fairly good policies by providing concessions to the payment system by way of 4. Campus through its promotion team tries to give a good image by providing maximum service quality.